Elevation-based upscaling of organic carbon stocks in High-Arctic permafrost terrain: a storage and distribution assessment for Spitsbergen, Svalbard - Niels Weiss; Samuel Faucherre; Nikos Lampiris; Robin Wojcik (Polar Research, 2017)
Accurate quantity and distribution estimates of permafrost soil organic carbon (SOC) stocks are needed to project potential feedbacks to climate, following warming. Still, upscaling from local field observations to regional estimates to circumarctic assessments remains a challenge. Here we explore elevation-based upscaling techniques for High-Arctic permafrost SOC stocks. We combine two detailed, high-resolution SOC inventories on Spitsbergen (Svalbard) with regional validation data. We find a clear relationship between elevation and SOC content, and use this observed exponential correlation, as well as discrete elevation classes, as upscaling models for Spitsbergen. We estimate the total amount of permafrost SOC currently present in soils on Spitsbergen to be 105.36 Tg (0.11 Pg), with a mean SOC content of 2.84 ± 0.74 kg C m−2 (mean ± 95% confidence interval). Excluding glaciers and permanent snowfields, exposed land is currently estimated to contain 6.26 ± 1.47 kg C m−2.